ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEBIJAKAN DIVIDEN (Studi Empiris Perusahaan Manufaktur yang Terdaftar di BEI Periode 2013-2016) - Nandita Putri Yuliani, 14.05.52.0054; Anggana Lisiantara, Gregorius (Students' Journal of Accounting and Banking, 2018)
This research was performed to examine the effect of variabele profitability, liquidity, leverage, growth, and firm size on dividend policy by manufacturing companies listed on the Stock Exchange of Indonesia from 2013 to 2016. The profitability as measured by ROA, liquidity as measured by CR, leverage as measured by DER, growth as measured by sales growth, and firm size measured with the natural log of total asset and dividend policy with Devidend Payout Ratio. The population of this research is 151 manufacturing companies listed on the Stock Exchange od Indonesia from 2013 to 2016. The sampling technique used was purposive sampling with specified criteria. Data obtained from the publication official website BEI (www.idx.co.id). Obtained a sample 107sample data. The analysis technique used is multiple regression. The results of profitability and liquidity has not significant. Leverage, growth, and firm size has a significant withdividend policy. Keyword: profitability, liquidity, leverage, growth, firm size, and dividend policy